University Extension of Health Care: Multiprofessional care for people with cleft lip and palate - Da Ré, Allessandra Fraga; Sepulveda, Consuelo de Los Angeles Vielma; Schilling, Gabriela Ribeiro; Kniphoff, Gustavo Jungblut; Silveira, Vanessa dos Santos; Grzybowski, Luciana Suárez; Barbosa, Lisiane De Rosa; Maahs, Marcia Angelica Peter; Machado, Márcia Salgado; Cardoso, Maria Cristina de Almeida Freitas (Seven Editora, 2023)
Introduction: University extension enables a connection of the learning of students and teachers with the community, having multidirectional benefits for comprehensive and multidisciplinary health care. On the other hand, one of the most common congenital craniofacial malformations are cleft lip and palate (CLP), which need multidisciplinary attention from birth to optimize the process of habilitation and rehabilitation in health and monitor individual neuropsychological development. Objective: To report an extension proposal in health care for people with CLP. Materials and Methods: This is an experience report of an extension action in health care for children and adolescents with CLP. Results: This extension proposal counts on the interdisciplinary attention of the speech therapy, odontology, physiotherapy and psychology areas and, multidisciplinary of the medical area. The purpose of this extension activity involves the reception, habilitation of oral functions, neuropsychological development and rehabilitation of people with CLP. Conclusions: The reception and health care of individuals with CLP and their families can benefit from health care activities through university extension. DOI: https://doi.org/10.56238/colleinternhealthscienv1-091